Innovation cooperation networks: case of a multisectoral and interdisciplinary partnership - Alves, J. (2012)
Network cooperation processes gained special interest in the new knowledge economy as they provide better conditions to innovation and knowledge creation and diffusion. Although the importance of this strategic tool has been increasingly recognized, individualistic behaviour tends to prevail within small and medium-sized firms and many of them continue to exhibit an attitude of resistance when dealing with collaborative experiences. This paper has two main goals. First, it explores how networks can promote innovation and help overcome the difficulties inherent in cooperation processes. Second, it illustrates an innovative approach to network cooperation in a multisectoral and inter-disciplinary environment, presenting the experience of the “House of the Future” network in Aveiro, Portugal.